Reverse innovation : create far from home, win everywhere - Govindarajan, Vijay; Trimble, Chris (Boston : Harvard Business Press, 2012)
'The popular HBR article'How GE is Disrupting Itself' by GE's CEO Jeffrey Immelt, Vijay Govindarajan, and Chris Trimble first coined the term reverse innovation, using it to describe GE's new approach to global strategy. GE, like most multinationals, follows a strategy of developing products at home and then adapting them for other markets around the world. But as growth accelerates in emerging markets and slows in developed ones, GE is also now doing the reverse: developing products in countries like China and India, and then distributing them globally. As the tip of the multinationals iceberg, GE shows that successful global companies will have to do both. But succeeding at reverse innovation requires a different model than the one used in home markets. This book picks up where the ground-breaking HBR article leaves off, and goes beyond describing the reverse innovation phenomenon to showing how to do it. Through eight detailed case studies - PepsiCo, Procter and Gamble, EMC, Deere & Company, Logitech, Harman International , PIH/PACT, and, of course, GE - authors Govindarajan and Trimble explain how to succeed on the ground with reverse innovation, showing how these companies use a different management model than the one they use in their home markets. This book explains the new model these companies use -- the Local Growth Team -- and how it works, and offers a'Reverse Innovation Toolkit' providing readers with a step-by-step action plan for developing and implementing their own reverse innovation strategies.'--
Keywords: International business enterprises -- Management -- Case studies; Technological innovations -- Management -- Case studies; Strategic planning -- Case studies